GON, WOO, SEONDO GODDESS, AND CHINESE LEGENDS ABOUT PEOPLE IN KOREAN MYTHOLOGY - PARK, Jong-seong (International Journal of Korean Humanities and Social Sciences, 2016)
Gon and Woo are mythological persons who were born in China and who performed all their tasks there. That is why they are present in Korean myths from time to time, for instance in the myth about Dangun or the kingdom Goguryeo, and finally they achieve universality and credibility. On the other hand the holy mother Seondo was the daughter of the Chinese emperor who acquired supernatural powers and went to Korea where she stayed. Consequently Koreans did not know much about what she did in China. As a result she became accepted by Koreans as the common goddess of mountains called differently in different regions. From the point of view of the Korean nation Ju Wonjang and Seol Ingwi are heroes from China but at the same time despite being persons of low birth as commonalty they managed to become heroes. It is an extremely important aspect for Koreans. Although they actually attacked Goguryeo and forced Korea to obey China, for the Korean commonalty such historical experiences could be of different significance. As far as myths about Chinese heroes are concerned, the Korean commonalty seemed to be interested first and foremost in their skills and strength, which were so great that there was no authority in Korea powerful enough to withstand it. In my opinion for the Korean commonalty the concept of nation was something in the form of an imaginary community, which should arise at any moment by chance and should unify people strongly. The Korean commonality expressed in legends and folktales its strong will to identify themselves with people beyond national divisions in order to save themselves from their hard everyday life. Folktales usually do not present any issue fully. They only present a specific situation or a particular day or something typical of China, etc. By treating Chinese heroes as if they were their own, the Korean commonalty took advantage of them in some sense. I think it was their strategy enabling them to fulfil their dreams by living the life of others.